Inactivation of myostatin by photooxygenation using functionalized d-peptides. Issue 2 (26th January 2023) - Okamoto, Hideyuki; Murano, Shuko Amber; Ikekawa, Kaoru; Katsuyama, Masahiro; Konno, Sho; Taguchi, Akihiro; Takayama, Kentaro; Taniguchi, Atsuhiko; Hayashi, Yoshio
Abstract : Myostatin-binding d -peptides functionalized with photocatalyst efficiently inactivate myostatin by photooxygenation and show no phototoxicity and high resistance to proteolytic enzymes, leading to the treatment of muscular atrophic diseases. Abstract : Inhibition of myostatin is an attractive strategy for the treatment of muscular atrophic diseases such as muscular dystrophy. For the efficient inhibition of myostatin, functionalized peptides were developed by the conjugation of a 16-mer myostatin-binding d -peptide with a photooxygenation catalyst. These peptides induced myostatin-selective photooxygenation and inactivation under near-infrared irradiation, and were associated with little cytotoxicity or phototoxicity. The peptides are resistant to enzymatic digestion due to their d -peptide chains. These properties could contribute to the in vivo use of photooxygenation-based inactivation strategies targeting myostatin.